Keabsahan Jual Beli Non-Fungible Token (Nft) pada Metaverse yang Dimiliki oleh Ransverse Ditinjau dari Kitab Undang-Undang Hukum Perdata dan Kompilasi Hukum Ekonomi Syariah - Muhammad Azis Ramdhani Sobari Afiatin; Neni Sri Imaniyati; Diana Wiyanti (UNISBA Press, 2024)
ABSTRACT. The metaverse is a simulated digital environment that combines augmented reality, virtual reality, block chain, and social media to create user interaction areas that mimic the real world. It uses the block chain to ensure the uniqueness of digital goods, and non-fungible tokens (NFT) are unique and non-duplicable cryptographic tokens on the blockchain. NFT represent collectible digital assets with the same value as physical assets. However, Indonesian law does not provide specific rules for the metaverse and NFT. This research aims to describe the validity of buying and selling NFT on the metaverse, using a statutory approach method, conceptual approach method, normative juridical data collection type, analytical descriptive research specifications, and qualitative data analysis techniques. Ransverse, a virtual land buying and selling platform, does not meet the requirements of the